Pedoman, Bentuk dan Teknik Pelaksanaan Fungsi Pengawasan DPRD - Sarkawi - (Jatiswara, 2015)
The purpose of this study was to determine the Guidelines, Forms and Technical Implementation oversight function of Council. This research uses normative research with the approach of legislation and conceptual approaches. Research results can be concluded that the Guidelines on the oversight function of Parliament to the Regional Government in UUDN RI In 1945, Law No. 23 Year 2014 About Local Government, Law 27 Year 2009 on MPR, DPR, DPD and DPRD, PP 16 Year 2010 on Guidelines for Preparation of the Regional Representatives Council Regulation on the Rules of the Regional Representatives Council, and Regional Representatives Council Regulation district or local town. Implementation forms of oversight function of Parliament is done in the form of hearings, visit Working, Forming Tools Other Fittings required and formed by the plenary session, the Supervisory About Goods and Services Management, Process Monitoring On Procurement of goods and services and Supervision On Government Performance, as well as the recess. Technics implementation oversight functions, among others; (1) Respond to Public Complaints; (2) Monitoring Unit to Service; (3) Monitoring to SKPD; (4) Monitoring the Regional Head.